Crystal structures and Hirshfeld surface analyses of (N-hexyl-N-methyldithiocarbamato-κ2 S,S′)triphenyltin(IV) and [N-methyl-N-(2-phenylethyl)dithiocarbamato-κ2 S,S′]triphenyltin(IV) - Rapidah Mohamad,; Normah Awang,; Nurul Farahana Kamaludin,; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2018)
The crystal and molecular structures of two triphenyltin dithiocarbamate compounds, viz. [Sn(C6H5)3(C8H16NS2)], (I), and [Sn(C6H5)3(C10H12NS2)], (II), are described. The dithiocarbamate ligand in each molecule coordinates in an asymmetric fashion resulting in heavily distorted tetrahedral C3S coordination geometries for the Sn atoms, with the distortions traced to the close approach of the non-coordinating thione-S atom. The molecular packing in both compounds features C—H....Sn-phenyl) interactions. In (I), the donors are Sn-phenylC—H groups leading to centrosymmetric aggregates, while in (II), the donors are both Sn-phenyl-C—H and methyl-C—H groups leading to supramolecular chains propagating along the b axis. The identiﬁed aggregates assemble into their respective crystals with no directional interactions between them. An analysis of the Hirshfeld surfaces show distinctive patterns, but an overwhelming predominance (>99% in each case) of H...H, C...H/H...C and S...H/H...S contacts on the respective Hirshfeld surface.